Efficient management of the water resource in the fresh-cut industry: Current status and perspectives. Issue 2 (December 2015) - Manzocco, Lara; Ignat, Alexandra; Anese, Monica; Bot, Francesca; Calligaris, Sonia; Valoppi, Fabio; Nicoli, Maria Cristina
Abstract: Among the different food industries, fresh-cut produce manufacturing is one of the major water-intensive, due to the huge consumption of potable water to perform washing operations required to guarantee the safety and quality of the product. Reducing the water footprint of washing is thus a challenge for fresh-cut industries and food researchers. This review paper examines the current status of the water resource management in the fresh-cut industry and critically describes a comprehensive approach to the improvement of the water use efficiency by implementing strategies of water recirculation, reuse and recycling. In particular, advantages and limitations of chlorine and chlorine-free disinfectants to reduce water turnover in washing tanks were considered. In addition, particular attention was focussed on innovative technological solutions, based on either physical or chemical stresses, which could be exploited individually or in combination to treat wastewater deriving from fresh-cut washing and allow its recycling within the processing plant. Highlights: Sanitizing of fresh-cut vegetables is highly water-intensive. Proper management of in tank water recirculation decreases water footprint. Water recirculation, reuse and recycling dramatically contribute to water saving.